Preparation and microstructural characterization of five-layered aluminium-aluminium oxide functionally graded material - Maziyana, Marzuki; Noor Mazni, Ismail; Muhammad Ihsan, Abdul Latiff (IOP Publishing, 2021)
In this research, the metallic phase Aluminium (Al) and the ceramic phase Aluminium Oxide (Al2O3) were combined in different proportions for the preparation of five-layered Al-Al2O3 functionally graded material. Delamination or crack is the common problem at the metal-ceramic interface because of the large difference in material properties. Therefore, the main objective of this research was to investigate the defects within the layer during processing of the graded structure. The compositions of different weight percentages of five-layered structure are 100%Al+0%Al2O3, 95%Al+5%Al2O3, 90%Al+10%Al2O3, 85%Al+15%Al2O3 and 80%Al+20%Al2O3. During preparation of the graded composite structure, conventional two-step sintering cycle was followed. Heating rate 2°C/min, sintering temperature 630°C and sintering time 3 hours were maintained. It was observed that there was uniform distribution of Al2O3 ceramic particle in the Al matrix with the minimum of agglomeration, all interfaces were almost parallel with layers boundary and gradual transition occurred from first layer to fifth layer which confirmed the proper preparation processes of the five-layered graded composite structure. In addition, it was evident that there was no existence of crack within any layer or interface of the prepared composite structure.